Marketing Strategy to Increase Occupancy Rate at The Jayakarta Lombok Beach Resort & Spa, West Nusa Tenggara - Annisa Ramadhanty; I Ketut Suarja; Made Sudiarta; Indah Utami Chaerunnisah (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: This research aimed to determine the strengths, weaknesses, opportunities, and threats of marketing strategies in increasing occupancy rate at the Jayakarta Lombok Beach Resort & Spa, West Nusa Tenggara, Indonesia. Research methods: The analysis techniques used were quantitative Descriptive Analysis, Qualitative Descriptive Analysis, Internal Factor Analysis Summary (IFAS) Matrix, External Factor Analysis Summary (EFAS) Matrix, Internal - External (IE) Matrix, SWOT Analysis, and Quantitative Strategic Planning Analysis (QSPM) Matrix. Findings: Based on the results of IFAS matrix analysis, the main strength wasobtaining benefits from room usagein line with the reality from which room sales couldincrease hotel revenue. Based on the results of EFAS matrix analysis, the main opportunity was the government's policy related to the COVID19 pandemic with use the hotel as a place of isolation. Implication: The results of IE Matrix analysis put the company in the position of Growth Strategic (Cell II).